Review on the effect of student learning outcome and teaching technology in Omani's higher education institution's academic accreditation process - Tawafak, Ragad M.; Mohammed, Muamer N.; Ruzaini, Abdullah Arshah; Awanis, Romli (Association for Computing Machinery (ACM), 2018)
Academic accreditation standards are defined clearly in Higher Educational Institutions (HEI) plans, management, and delivering results of assessment student with learning outcomes. In recent years, all universities and institutions work hard to increase their approval privileges, skills, achievements through getting the accreditation from HEI. The aim of this integrative review was to examine the current evidence on the impact of technology learning on student learning and academic performance and analysis the main factors of an institution accreditation process. The authors searched several electronic databases for relevant articles, with different learning techniques. The main contribution of this study lies in showing the general criteria's of accreditation standards that focus on essential technology enhanced learning, student learning outcomes, and faculty technology experience on academic performance of universities. The result from this paper is showing the relations between what have been done and presented before with methods, factors, suggestions to identify these activities.